Governance and social information disclosure evidence from the UK. (2nd July 2007) - Parsa, Sepideh; Kouhy, Reza; Tzovas, Christos
Theoretically, corporate social responsibility should be embedded in corporate governance structures. This paper presents evidence that this is not the case for listed UK companies. Our evidence shows that in the presence of less stringent regulatory requirements, companies tend to disclose less social information in comparison to mandatory governance information. The observed positive association between social and governance information disclosure levels provides supporting evidence that companies with more transparent governance structures tend to be socially conscientious. The paper also empirically shows that the level of social information disclosure tends to vary with the size and industrial affiliation of companies, providing further evidence that listed UK companies are still treating social information as a tool to project a legitimate image.